Utilization of Water Hyacinth (Eichornia crassipes) as Liquid Organic Fertilizer (POC) on Chinese Cabbage (Brassica rapa var. parachinensis). - Frilly Kawet; Jeany Sh. Mandang; Beatrix Doodoh; Stanley A. F. Walingkas; Rinny Mamarimbing; Pemmy Tumewu (Jurnal Agroekoteknologi Terapan, 2023)
This study aims to examine the utilization of water hyacinth (POC) on the growth and yield of Chinese cabbage and to determine the best concentration to improve the growth and yield of Chinese cabbage. The research was conducted in Tara-tara Village, Tomohon District, Tomohon City. The research design used a completely randomized design (CRD) consisting of 5 treatments and 4 replications, making a total of 20 plots: 0% (P0), 10% (P1), 20% (P2), 30% (P3), and 40% (P4). The observed variables were plant height, number of leaves, and wet weight of the plant. The results showed that water hyacinth POC had an effect on plant height in the fourth week after transplanting. It also had a significant effect on the wet weight of Chinese cabbage after harvest. The best concentration of water hyacinth LOF was achieved at a concentration of 40%. Keywords: Chinese cabbage, Liquid Organic Fertilizer, Concentration. Keywords; Growing medium, Roasted Rice Husk, Mustard plants Abstrak Penelitian ini bertujuan untuk mengkaji pemanfaatan pupuk organic cair (POC) eceng gondok terhadap pertumbuhan dan hasil tanaman sawi hijau dan mendapatkan konsentrasi terbaik untuk meningkatkan pertumbuhan dan hasil tanaman sawi hijau. Penelitian ini dilaksanakan di Desa Tara-tara, Kecamatan Tomohon, Kota Tomohon. Rancangan penelitian ini menggunakan rancangan acak lengkap (RAL) yang terdiri dari 5 perlakuan dan 4 ulangan sehingga berjumlah 20 petak yaitu perlakuan 0 (P0), 10% (P1), 20% (P2), 30% (P3), 40% (P4). Variabel yang diamati : tinggi tanaman, jumlah daun, dan berat basah tanaman. Hasil penelitian menunjukkan bahwa POC eceng gondok berpengaruh terhadap tinggi tanaman pada minggu keempat setelah pindah tanam. Juga berpengaruh nyata pada berat basah tanaman sawi hijau setelah panen. Konsentrasi POC eceng gondok terbaik dicapai pada konsentrasi 40%. Kata Kunci: Sawi Hijau, Pupuk Organik Cair, Konsentrasi